Assessment of capacity auctioning mechanism for solar photovoltaic systems - Poullikkas, Andreas (My University, 2014)
In this work, an assessment of the integration of renewable energy sources for power generation (RES-E) using RES-E capacity auctions is carried out for different solar photovoltaic (PV) capacity electricity prices. The optimization model used is based on a genetic algorithm (GA) technique for the calculation of the required RES-E levy (or green tax) in the electricity bills. Also, this GA procedure enables the estimation of the level of the adequate feed-in-tariff to be offered to future RES-E systems, which do not participate in the capacity auctioning procedure. The results obtained, in the case of PV capacity auctioning for commercial systems, indicated that the required green tax, in order to promote the use of RES-E technologies, which is charged to the electricity customers through their electricity bills, is reduced with the reduction in the final auctioning price. This has a significant effect related to the reduction of electricity bills.
Keywords: Capacity auctioning; Photovoltaics; Renewable energy sources